The queen of the sports with the eyes of the women - Béki, Piroska; Keresztesi, Katalin (Acta Agraria Debreceniensis, 2017)
The media plays a very important role in the gender socialization as in the sport selection also, in which the individual is born,. We want to introduce those disciplines through the development of more studies are in athletics not least, belonged to a man’s privilege. The emergence of women in a variety of masculine competitions has enabled the track and field sport turned into both gender sport. The masculinity and feminity separation in sport is increasingly disappear and become neutral. In our study, we analyze the changes in women’s athletics point of view of history, in some disciplines for women and the availability of representatives assessment of Hungary. We based on Methenys categorization in 1965, and Bem’s study, written in 1974, and examined women’s branch of track and field sports acknowledgment and acceptance focused on the masculine category.